Rational design of particulate vaccine adjuvants for enhanced T cell-mediated immunity - Huete Carrasco, Jorge (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2025)
Resolving the mechanisms underlying the immunostimulatory properties of vaccine adjuvants is critical to provide a basis for rational adjuvanted vaccine design for specific diseases and target groups. Building on this, there is a need for adjuvants that more effectively promote T cell-mediated immune responses, particularly CD8+ T cells, Th1 cells and IFN-y production, for viral and cancer vaccines. Over recent years, the size of particulate adjuvants has emerged as a key parameter influencing adjuvanticity. Previous work from the Lavelle lab demonstrated that size is a key factor in the induction of CD8+ T cell responses by polystyrene and poly D,L-lactic-co-glycolic acid particles. In this thesis, the importance of adjuvant particle size was addressed with oil-in-water emulsions. It was found that the efficacy of emulsion-based vaccine adjuvants in promoting T cell-mediated immunity depends on the composition of the emulsion, and the effectiveness of the most efficient system can be further enhanced by reducing droplet size. A 60nm squalene-in-water emulsion containing a saponin and a synthetic TLR-4 ligand (SMQ) was the most effective adjuvant at enhancing antigen-specific T cell and antibody responses. Conventional type 1 dendritic cells were essential for vaccine-induced T cell-mediated immune responses, promoting the cross-presentation of exogenous antigens. Vaccination with antigen and the 60nm SMQ adjuvant was effective in a therapeutic cancer setting, and this was further enhanced by combination with anti-PD-1 blockade therapy. In the second part of this thesis, the importance of antigen location in particulate adjuvant formulations was investigated. While oil-in-water emulsions do not require antigen association with the adjuvant for vaccine efficacy, this is less clear with polymeric nanoparticles. Antigen adsorption to 50nm polymeric particles was crucial to enhance antigen-specific CD8+ T cell responses, and conventional type 1 dendritic cells were the key mediator of these responses. The adsorption of antigen to polymeric nanoparticles was essential to enhance the anti-tumour response in a therapeutic cancer setting, and this response was further improved by synergy with anti-PD-1 blockade therapy. Overall, this work advances our understanding of how the physicochemical properties of adjuvants dictate their efficacy and potential in the development of prophylactic vaccines for existing and emerging intracellular pathogens, as well as therapeutically in the context of cancer vaccines.
APPROVED
Keywords: rational design; adjuvants; polymeric nanoparticles; oil-in-water emulsions; physicochemical properties; dendritic cells; vaccines; T-cell mediated immunity; antibodies; intracellular pathogens; cancer; immune checkpoint inhibitors